Resistência à fratura de diferentes núcleos de preenchimento com compósitos bulk fill em dentes com extensa destruição coronária - Oliveira, Carlos Rangel de Moura [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
This study aimed to evaluate the ultimate fracture strength and failure modes of different core techniques associated with intraradicular fiberpost in bovine mandibular lateral incisors with extensive coronary destruction. Forty teeth were prepared endodontically, randomly divided into 4 experimental groups (n=10) and a fiberpost (Whitepost DC0.5) was cemented with LuxaCore Z for all groups. The core was confeccioned, after obtaining a 1.0 mm cervical ferrule, with: FOBF-Filtek One Bulk Fill; FZ350- Filtek Z350 XT; FBFF-Filtek Bulk Fill Flow; and LCZ-LuxaCore Z. Total zirconia crowns (Y-TZP) produced by CAD/CAM were cemented with RelyX U200. After storage in distilled water at 37ºC for 48 h, the specimens were submitted to thermal cycling (10,000 cycles, 5- 55ºC, 30 s dwell time) and, afterwards, to the mechanical test of compressive strength fracture (1.0 mm / min) at 135º along the tooth axis in electromechanical machine (EMIC DL2000). The ultimate load supported by each specimen was recorded in Newton. The fracture mode was classified by means of stereomicroscopic loupe analysis (30X). The fracture strength data were analyzed by the non-parametric Kruskal-Wallis test, followed by the post-hoc Dunn test. The data of the fracture modes were analyzed by Fisher's exact test (α=0.05). No significant differences (p>0.05) were observed among the FOBF, FZ350 and FBFF groups (mean ranks= 20.30, 12.20 and 23.20, respectively). LCZ (mean rank= 26.30) produced similar results to those of FOBF and FBFF (p>0.05) and higher than those of FZ350 (p=0.042). The most frequent type of failure was irreparable, regardless of the experimental condition. The lowest percentages of reparable fractures were 10% for the FOBF group, followed by 20% of LCZ. The use of bulk fill materials, including the “core-and-post” LCZ composite, did not impair the ultimate fracture strength of endodontically treated teeth with extensive coronal destruction. The use LCZ made it possible to perform the procedures in fewer steps and less clinical time, without impairing the fracture resistance of endodontically treated lateral incisors.

Este estudo objetivou avaliar a resistência máxima e o padrão de fratura de diferentes técnicas para núcleo preenchimento associados a pinos de fibra de vidro em incisivos laterais inferiores bovinos com extensa destruição coronária. Quarenta dentes foram preparados endodonticamente, divididos aleatoriamente em 4 grupos experimentais (n=10) e um pino de fibra de vidro (Whitepost DC0,5) foi cimentado com LuxaCore Z para todos os grupos. A confecção dos núcleos de preenchimento foi realizada, após obtenção de férula cervical de 1,0 mm, com: FOBF-Filtek One Bulk Fill; FZ350- Filtek Z350 XT; FBFF-Filtek Bulk Fill Flow; e LCZ-LuxaCore Z. Coroas totais de zircônia (YTZP) produzidas em CAD/CAM foram cimentadas com RelyX U200. Após armazenamento em água destilada a 37°C por 48 h, os corpos-de-prova foram submetidos a ciclos térmicos (10.000 ciclos, 5-55ºC, banhos de 30s) e, posteriormente, ao ensaio mecânico de resistência à fratura por força compressiva aplicada (1,0 mm/min) em 135º ao longo eixo do dente em máquina eletromecânica (EMIC DL2000). A força máxima suportada por cada espécime foi registrada em Newton. O modo de fratura foi classificado por meio de análise em lupa estereomicroscópica (30X). Os dados de resistência à fratura foram analisados pelo teste não paramétrico de KruskalWallis, seguido pelo post-hoc teste de Dunn. Os dados dos padrões de fratura foram analisados pelo teste exato de Fisher (α=0,05). Não foram observadas diferenças significativas (p>0,05) entre os grupos FOBF, FZ350 e FBFF (ranks médios= 20,30, 12,20 e 23,20, respectivamente). LCZ (rank médio= 26,30) produziu resultados semelhantes aos de FOBF e FBFF (p>0,05) e superiores aos de FZ350 (p=0,042). O tipo de falha mais frequente foi irreparável, independentemente da condição experimental. As menores porcentagens de fraturas reparáveis foram de 10% para o grupo FOBF, seguidas por 20% de LCZ. A utilização de materiais bulk fill, incluindo o compósito “core-and-post” LCZ, não prejudicou a resistência máxima à fratura dos dentes tratados endodonticamente com extensa destruição coronária. A utilização do LCZ possibilitou a realização dos procedimentos em menos passos e menor tempo clínico, sem prejudicar a resistência à fratura de incisivos laterais tratados endodonticamente.
Fracture strength of different core build up with bulk fill composites in teeth with extensive coronary destruction
Keywords: Post and core technique; Dental restoration permanent; Resin cements; Composite resins; Dental restoration failure; Restauração dentária permanente.; Cimentos de resina.; Resinas compostas; Falha de restauração dentária.; Técnica de retentor intrarradicular